Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages COMMON WEALTH INFORMATION BULLETIN 4 GOWER STREET CW LONDON W.C.1 POVERTY AND INEQUALITY 1. — Incomes below the Minimum. 2. — Inferior Education. 3. — Malnutrition. 4. — Ill-health. 5. — Slums and Overcrowding. 6. — Capitalism's Palliatives. 7. — How Poverty can be Abolished. 8. — Questions for Discussion. 9. — Reading List. No. 6 October, 1944 6d. REVISED PRICE 9D. 15X/2/98/13